The Spanish worldview concerning Buddhism in the Kingdom of Siam at the end of the 19th Century - ทิพยศักดิ์, สถาพร (Journal of Buddhist Studies Chulalongkorn University, 2019)
The article presents an account concerning Buddhism in Siam at the end of the 19th Century by Melchor Ordonez y Ortega, a courtier of Queen Isabella II during the journey of the mission of the delegation in Indochina for to survey and assess the situation in their overseas colonies when the Spanish empire finally began to see it decline. Melchor’ s descriptions cover the three main elements of Buddhism: Buddha, the Buddhist doctrines and the Sangha community. This evidence is considered one of the most important historical documents.